PENGARUH MODAL, TENAGA KERJA, LAMA USAHA TERHADAP PENDAPATAN DENGAN TEKNOLOGI SEBAGAI VARIABEL MODERATING (Studi pada Kelurahan Wonokoyo Kecamatan Beji Pasuruan) - Sugeng Hariadi; Saviratuz Zahro (POLITEKNIK LP3I JAKARTA, 2024)
This research aims to understand the influence of capital, labor, length of business on income with technology as a moderating variable. This research uses an associative quantitative method, with a minimum sample size of 50 respondents, using multivariate (correlation or multiple regression), the tests used in this research use descriptive statistical analysis, instrument reliability tests, validity tests, reliability tests, classical assumption tests, normality test, heteroscedasticity test, multicollinearity test, multiple linear regression analysis, T test, r test. The results of the research show that 1. capital (X1) has a significant effect on income (Y) the sig value obtained is 0.00 > 0.05, so that H0 is accepted 2. labor (X2) has a significant effect on income (Y) the significant value is obtained is 0.000 < 0.05, so H0 is accepted 3. Length of business (X3) has a significant effect on income (Y). The significant value obtained is 0.00 < 0.05, so H0 is accepted 4. Interaction variable between Capital and Technology ( X1Z) has a significant effect on Income (Y) with a significant value of 0.000 < 0.05. Therefore, H0 is accepted 5. The interaction variable between Labor and Technology (X2Z) has a significant influence on Income (Y) with a significant value of 0.003 < 0.05. Therefore, H0 is accepted. 6. The interaction variable between Business Length and Technology (X3Z) has a significant influence on income (Y). The significant value is 0.000 > 0.05, meaning H0 is accepted.